2018
DOI: 10.1007/s00417-018-3959-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of fall-related open globe injuries in Japan

Abstract: Fall-related open globe injuries were more frequent in elderly female and accompanied by larger wound lengths and severer ocular complications. Visual outcomes in patients with fall-related open globe injuries were related to initial visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Male predominance at younger age may be associated with occupational exposure and risk-taking behavior (higher incidence of assault, sport, and traffic accident-related ocular injuries) [ 15 ]. However, a change in male/female proportion was observable in older ages, as we found a female predominance (69.2%) in people older than 70 years, similar to the study by Vidne-Hay et al [ 16 ], which may be related to the suggestion that elderly women with osteoporosis have an increased risk of falling and sustaining injuries [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Male predominance at younger age may be associated with occupational exposure and risk-taking behavior (higher incidence of assault, sport, and traffic accident-related ocular injuries) [ 15 ]. However, a change in male/female proportion was observable in older ages, as we found a female predominance (69.2%) in people older than 70 years, similar to the study by Vidne-Hay et al [ 16 ], which may be related to the suggestion that elderly women with osteoporosis have an increased risk of falling and sustaining injuries [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, road traffic, work, and falling were the major circumstances at risk, however, distinct patterns can be observed in different age groups. Additionally, a study of Morikawa et al demonstrated a significantly higher proportion of globe rupture (91%) in fall-related OGI patients, predominantly in the elderly women group, compared to the non-fall-related group (38%) 23 . Our study also confirmed that falling was the situation with a high susceptibility of globe rupture, particularly in the elderly 23,[26][27][28] .…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the inhomogeneous distribution of affected age groups may reflect different daily activities of the at risk populations, therefore the demographic data should be taken into consideration when implementing the safety measurements in each country. www.nature.com/scientificreports/ Some specific circumstances were more likely to cause globe rupture than others [18][19][20][21][22][23] . A study by Feng et al reported that violence, explosion, and traffic were the most frequent causes leading to severe ruptured eyes requiring vitreoretinal surgery 24 .…”
Section: Discussionmentioning
confidence: 99%
“…RD occurred within 24 h of open globe injury in only 27% of cases 22 . Retinal detachment and initial VA were also reported as risk factors of poor final VA in studies of open-globe injuries 23 . OTS includes these major risk factors and is a good overall predictor for final VA in our study.…”
Section: Discussionmentioning
confidence: 99%